ANALYTICAL STUDY OF THE DYNAMIC CHARACTERISTICS OF DIFFERENT CONSTRUCTION SOLUTIONS OF SCHOOL BUILDINGS IN THE CITY OF FERGANA - B.B. Oktamov (European Science Publishing, 2023)
In the article, the seismic and constructive aspects and dynamic characteristics of secondary school buildings of different sizes and constructions in Fergana city are studied.
Keywords: National, cultural, resource, education, mechanism, innovation.